Yasynetska O. A. Metaphoric categorization of conceptual pictures - Yasynetska O. A. (Philological Treatises, 2020)
The author of the article analyzes the inability of the conceptual approach, which is highly popular in contemporary linguistic studies, to serve as methodological basis for translating language items that constitute lingual expression of identical or similar concepts in different languages. The suggested model of translating metaphors integrates attention to both conceptual and lingual peculiarities of metaphors across languages.